AUDIT SISTEM INFORMASI DAN PERAN AUDITO - Mumu Muzaemi (LPPM POLITEKNIK LP3I BANDUNG, 2016)
Information system auditing is intended to collect and evaluate evidences to know if a computer system is able to safeguard assets and maintain data integrity so that the goals of organization can be reached effectively and efficiently. The auditors can audit using three approaches such as audit around the computer; audit through the computer and audit with the computer. In addition, Auditors should consider the risks and related controls mainly general control and application control. Audit techniques which can be applied include integrated test facility, embedded audit routine, extended record, snapshot, control flowcharting, mapping, and using audit software such as ACL, IDEA, Microsoft Excel or Microsoft Access. In this context, auditors are required to improve their skills related to information technology